Textbook Alternative Incentive Programs at U.S. Universities: A Review of the Literature - Lierman, Ashley (Evidence Based Library and Information Practice, 2020)
Objective – This article reviews current literature on incentive grant programs for textbook alternatives at universities and their libraries. Of particular interest in this review are common patterns and factors in the design, development, and implementation of these initiatives at the programmatic level, trends in the results of assessment of programs, and unique elements of certain institutions’ programs.Methods – The review was limited in scope to studies in scholarly and professional publications of textbook alternative incentive programs at universities within the United States of America, published within ten years prior to the investigation. A comprehensive literature search was conducted and then subjected to analysis for trends and patterns.Results – Studies of these types of programs have reported substantial total cost savings to affected students compared to the relatively small financial investments that are required to establish them. The majority of incentive programs were led by university libraries, although the most successful efforts appear to have been broadly collaborative in nature. Programs are well-regarded by students and faculty, with benefits to pedagogy and access to materials beyond the cost savings to students. The field of replacing textbooks with alternatives is still evolving, however, and the required investment of faculty time and effort is still a barrier, while inconsistent approaches to impact measurement make it difficult to compare programs or establish best practices.Conclusion – Overall, the literature shows evidence of significant benefits from incentive programs at a relatively low cost. Furthermore, these programs are opportunities to establish cross-campus partnerships and collaborations, and collaboration seems to be effective at helping to reduce barriers and increase impact. Further research is needed on similar programs at community colleges and at higher education institutions internationally.